Current Problems of Preventing Aggressive Behavior in the Educational Environment: A Case Study of Three Schools in the Russian Countryside - Marina P. Guryanova; Elena I. Selivanova (Peoples' Friendship University of Russia (RUDN University), 2021)
Among the most acute socio-pedagogical problems facing the modern Russian school is the increasing number of aggressive manifestations in the educational environment. This situation actualizes the schools need for the prevention and correction of aggressive behavior. The article presents the results of a socio-pedagogical research, the purpose of which was to identify the types and forms of aggressive behavior in the educational environment and to explore the current state of preventive work. The study was conducted by the Institute for the Study of Childhood, Family and Upbringing in July 2021 in the form of a questionnaire survey of directors of educational organizations. The methodology of the research included a socio-pedagogical analysis of situations of aggressive manifestations among students, teachers and parents; study of social, environmental, family and personal factors of aggressive behavior; and identification of mechanisms for preventing aggressive behavior in the educational environment. The results are presented in the format of socio-psychological portraits of three schools located in the countryside, which are prominent representatives of Russian rural society. The study made it possible to draw the following main conclusions: (1) preventive work becomes an independent type of pedagogical work; (2) cyber-aggression, which was actively manifested during the period of distance learning and now requires comprehensive preventive work with students, teachers, and parents, is an over-pressing problem for educational organizations; (3) todays school is faced with the urgent task of developing and implementing programs for the prevention and correction of aggressive behavior. The ideas presented in the article can be used in the practice of educational organizations of different types.